2021
DOI: 10.1002/aet2.10574
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal accuracy analysis of ultrasound performed during a four‐year emergency medicine residency

Abstract: Point-of-care ultrasound (POCUS) training is well-established in emergency medicine (EM) residency programs in the United States. Demonstration of competency in POCUS has been required for graduates of United States EM residencies since 2001, yet EM resident POCUS education strategies vary widely. 1-4 In 2013, the American College of Emergency Physicians (ACEP), the Society for Academic Emergency Medicine (SAEM), and the Council of Emergency Medicine Residency Directors (CORD) published general guidelines for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Indeed, an insufficient number of peer-reviewed ultrasound examinations could prevent trainees in the STS group to reach interpretation plateau for each imaging spot 33 . Schleifer et al 34 also showed that POCUS usage decreased over the residency as well as accuracy to the diagnosis if not maintained by additional educational initiatives such as refresher rotations. This is a pivotal fact, in particular when certification is not part of the curriculum 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an insufficient number of peer-reviewed ultrasound examinations could prevent trainees in the STS group to reach interpretation plateau for each imaging spot 33 . Schleifer et al 34 also showed that POCUS usage decreased over the residency as well as accuracy to the diagnosis if not maintained by additional educational initiatives such as refresher rotations. This is a pivotal fact, in particular when certification is not part of the curriculum 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, we found that not all studies evaluating HINTS were in AVS and maintain proficiency at HINTS, STANDING algorithm, VOG, etc. [92][93][94] ; understanding cognitive biases that inhibit knowledge uptake 95 ; exploring the role of shared decision making regarding more expensive or invasive test options when diagnostic uncertainty persists 96 ; and finally, designing implementation sciencebased approaches to accelerate a more efficacious and effective ED dizziness evaluation since traditional medical education and publications have not altered this paradigm.…”
Section: M Itati O N Smentioning
confidence: 99%
“…The next steps in research include standardized approach to patients with dizziness and vertigo into syndromes by timing and triggers including AVS and episodic vestibular syndrome; standardization of diagnostic criteria; quantifying reliability of the element of the history and the physical examination; training of providers in diagnostic maneuvers and treatment with canal repositioning when indicated; studies of reliability and reproducibility of training emergency physicians and other clinicians; assessing the method and duration of physician education to attain and maintain proficiency at HINTS, STANDING algorithm, VOG, etc 92–94 95 ; exploring the role of shared decision making regarding more expensive or invasive test options when diagnostic uncertainty persists 96 ; and finally, designing implementation science‐based approaches to accelerate a more efficacious and effective ED dizziness evaluation since traditional medical education and publications have not altered this paradigm.…”
Section: Limitationsmentioning
confidence: 99%
“…Although these numbers were originally based on expert opinions, there are now several studies supporting them [11][12][13][14][15]. Once a high level of skill has been acquired, it seems to be retained, although it might need continued training and supervision to maintain it at the optimal level [16].…”
Section: Introductionmentioning
confidence: 99%